ANALISIS POTENSI TENAGA SURYA PADA PERMODELAN BANGUNAN TIGA DIMENSI BERDASARKAN DATA OPEN STREET MAP (STUDI KASUS: UNIVERSITAS GADJAH MADA YOGYAKARTA) - Gilang Cahya Nusantara; Bondan Galih Dewanto (Elipsoida : Jurnal Geodesi dan Geomatika, 2020)
Energy crisis that occurred in the world after being exploited on a large scale against fossil energy caused people has to think again about renewable energy. In Indonesia, the electricity consumption always increases every year with fossil energy dominating energy sources. Based on the Government Regulation number 79 of 2014, concerning the National Energy Policy, the Government of Indonesia has a national target in the implementation of renewable energy of 23% in 2025 and 31% in 2050. Information disclosure and development of geospatial technology is shown through the availability of information on the dimensions, location, and the height of objects on the surface of the earth through the open street map (OSM) website, one of which is the building. Digital Elevation Model (DEM/DEMNAS) data can be accessed through the Geospatial Information Agency (BIG) website. Utilization of this information can be done by utilizing QGIS and ArcGIS Pro software. The existence of an energy crisis and technological developments led to calculate Solar Radiation (contained in ArcGIS Pro) which can calculate the solar potential at a location based on three-dimensional building data, DEM, and solar intensity. Universitas Gadjah Mada (UGM) has announced their commitment in realizing new and renewable energy in Indonesia. Therefore, researchers intend to find out the solar potential in the UGM region in order to realize government programs in the application of new renewable energy. Based on the analysis done in this research, we get the amount of solar energy potential of 369.543 kWh/ m2/ day. Through this research we hope that UGM can become a pilot campus in the application of renewable energy, solar energy and can reduce the use of conventional electricity using fossil energy.Keywords: Solar Energy Potential, Three Dimensional Building, Open Street Map, UGM.